2004
DOI: 10.1007/s00106-003-0944-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress associated with acute tinnitus

Abstract: Patients with acute tinnitus can be differentiated in terms of their distress and the psychological impairment caused by their symptoms. These results suggest that the immediate reaction to the manifestation of tinnitus might be of prognostic value for the level of emotional distress experienced in chronic tinnitus. The question arises of whether psychological intervention in the acute stage of tinnitus might be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…The threshold we used for the distinction between moderate and severe cases requires the presence of at least seven bothering somatic symptoms, and is seen as a reliable distinction between presence of somatoform disorders in comparison to their absence [28]. The present finding also is in line with observations that tinnitus patients with high levels of self- and somatic attention express greater emotional and tinnitus-related distress [35]–[37], and that depressed tinnitus patients display strong somatic focus resulting in a tendency to report large numbers of medically unexplained symptoms [36].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The threshold we used for the distinction between moderate and severe cases requires the presence of at least seven bothering somatic symptoms, and is seen as a reliable distinction between presence of somatoform disorders in comparison to their absence [28]. The present finding also is in line with observations that tinnitus patients with high levels of self- and somatic attention express greater emotional and tinnitus-related distress [35]–[37], and that depressed tinnitus patients display strong somatic focus resulting in a tendency to report large numbers of medically unexplained symptoms [36].…”
Section: Discussionsupporting
confidence: 85%
“…Longitudinal studies with a small number of acute tinnitus patients suggest that psychopathological conditions exist beforehand and constitute risk factors for the development of a distressing tinnitus or that they arise together with the tinnitus [33], [37]. This does not exclude the possibility, however, that tinnitus promotes the progression of psychopathologies and it appears likely that both developments exist.…”
Section: Discussionmentioning
confidence: 98%
“…This interpretation is corroborated by longitudinal studies, which suggest that depression and anxiety levels at tinnitus onset are related to the progression of tinnitus-related distress [3, 4]. Furthermore, it was observed that depression and anxiety in tinnitus sufferers decreased with time only in those tinnitus patients that did not exhibit personality disorders [9].…”
Section: Discussionmentioning
confidence: 81%
“…The distress associated with tinnitus shows closer relation with factors related to emotional health as depression, anxiety, and somatic symptom severity than with the loudness of the tinnitus [2]. Moreover, depression and anxiety were found to be enhanced at tinnitus onset in patients who later develop high tinnitus-related distress [3, 4] suggesting that emotional health may be prognostic for future tinnitus-related distress. It cannot be excluded, however, that distressing tinnitus adversely influences emotional health and that its association with depression and anxiety is overestimated due to content overlap in the questionnaires [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, the majority of EEG studies focused on differences between tinnitus and non-tinnitus subjects and did not account for psychological comorbidities although many tinnitus patients suffer from comorbid depressivity or anxiety [45], [46], which themselves might cause changes in oscillatory brain activity [47], [48]. We tested this in the present study and were unable to demonstrate an association between scores in the depressivity, somatization, or anxiety scales of the SCL-90-R questionnaire and band power.…”
Section: Discussionmentioning
confidence: 99%